Hubungan disiplin kerja dengan lingkungan kerja tenaga kesehatan di Puskesmas Kecamatan Kresek Kabupaten Tangerang - Ilham, Muhammad; Rino Vanchapo, Antonius (Vanchapo Health Science Journal, 2023)
Background Human resources certainly play a very important role in realizing an ideal organization, and need to get deeper attention and study, especially on how to carry out their responsibilities so that the results achieved will be in accordance with what is done, to achieve good goals. It takes someone who is disciplined, in addition to discipline the company must pay attention to the work environment of employees so that employees can work effectively and efficiently, because the work environment can affect a person in carrying out the tasks assigned either directly or indirectly. The benefit of the work environment is to create passion for work, so that productivity and work performance increase. Research Objectives This study aims to determine work discipline and work environment related to health workers at the health center. Kresek District, Tangerang Regency in 2022. Quantitative research method with a cross sectional study approach, using a sampling technique with total sampling. Data collection was carried out by distributing questionnaires to 63 respondents to health workers at the Kresek District Health Center, Tangerang Regency 2022. The results showed that most of the 63 respondents had high work discipline as many as 62 respondents (98.4%), out of 63 respondents most of them had a work environment high physical work as many as 61 respondents (96.8%), and 63 respondents mostly who have a high non-physical work environment as many as 62 respondents (98.4%). The results of the Spearman's rho statistical test showed that the value of work discipline with a physical work environment was ℓvalue = 0.000 which means lower than (ℓvalue > 0.05) inversely proportional to the results of work discipline with a non-physical work environment value ℓvalue = 0.900 which means higher than ( ℓvalue > 0.05). So it can be concluded that there is a significant relationship between work discipline and the physical work environment of health workers at the Kresek District Health Center, Tangerang Regency, in 2022.